ONLINE TEACHING BY DIGITAL NATIVE AND DIGITAL IMMIGRANT LECTURERS OF HIGHER EDUCATION - Agus Eko Cahyono; Yayuk Widyastuti Herawati; Abdul Muntaqim Al Anshory (International Journal of Innovative Technologies in Social Science, 2022)
The present study is aimed at taking a deep look at the differences between digital native and digital immigrant lecturers’ strategies in doing online learning in higher education. Online teaching is the teaching carried out not physically face to face between students and lecturer, rather by the use of any internet platform in distance. Digital native lecturers are lecturers born in the era of knowing the growth of technology and very familiar and skilled of operating any technological media of teaching (in this research, for those lecturers born after 1980). Digital immigrant lecturers are lecturers born in the era when the technology was not yet grown and popular and they still maintain to use conventional media of teaching (those lecturers born before 1980). The objectives of the present study are (1) to investigate how digital native lecturer is different from digital immigrant lecturer in the stage of implementation in teaching online courses for higher education student? This includes the problems such as their perception toward teaching online course, what platform they use for teaching online course, how they use the platform to implement and evaluate the online course; (2) to examine how digital native lecturer is different from digital immigrant lecturer in the stage of obstacles in teaching online courses for higher education student; (3) to elaborate how digital native lecturer is different from digital immigrant lecturer in the stage of overcoming obstacles in teaching online courses for higher education student. The findings of the present study provides insight on the practice of online teaching by both digital native and digital immigrant lecturers in higher education, then provides insight on the obstacles and strategies for solving them. Mostly (80%) of all lecturers have positive perception toward online teaching; merely five (mixed male and female lecturers) out of 21 lecturers who have negative perceptions and those are only digital immigrant lecturers (born before 1980) from different departments. Only few digital immigrant lecturers have negative perception toward online teaching. There are no disparity (no significant difference) between digital immigrant lecturers and digital native lecturers in terms of obstacles they face in online teaching as well as in solving the obstacles. Considering that there are many positive things in the use of technology in online teaching; in this case technology can optimize the quality of teaching, this can be the basis for universities broadly to make policies about the percentage of online teaching in the post-pandemic era with applicable terms and conditions. With background insight and the gap in technology literacy between digital native and digital immigrant lecturers, universities need to routinely provide training on the use of various technologybased platforms that support the optimization of teaching.